2019
DOI: 10.2196/10938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mobile App on Preoperative Patient Preparation for Major Ambulatory Surgery: Protocol for a Randomized Controlled Trial

Abstract: BackgroundInadequate preoperative patient preparation causes organizational, economic, and emotional problems to patients and professionals. In Spain, no current evidence is available on either the rate of compliance or the impact of good compliance with preoperative recommendations by patients in the ambulatory setting. However, it is known that around 25% of surgical cancellations in the major ambulatory surgery (MAS) are due to poor compliance with these recommendations and, therefore, avoidable. Introducin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
15
0
3
Order By: Relevance
“…The Listeo+ app provides personalized information to patients, reminders for preoperative recommendations, and a channel for various provider communications. Listeo+ is currently being tested in a multicenter RCT to evaluate the percentage of compliance to preoperative recommendations, thereby decreasing the rate of surgery cancellations [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Listeo+ app provides personalized information to patients, reminders for preoperative recommendations, and a channel for various provider communications. Listeo+ is currently being tested in a multicenter RCT to evaluate the percentage of compliance to preoperative recommendations, thereby decreasing the rate of surgery cancellations [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since our thematic analysis identified a major theme of being able to visually see where to go on the day of surgery, we felt it was appropriate to focus on an ACH-specific resource. We found that a variety of generic (non-site specific) applications or online videos are available for surgical preparation [ 12 , 13 , 14 ] and we are continuing to explore options for further development of a site-specific app. A strength of our study was the ability to directly compare a family’s sense of preparedness for surgery with and without accessing the in-person Surgery 101 program.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that there may be a convenient approach to communication between ambulatory surgery patients and HCPs. Because an increasing number of surgeries are being performed as ambulatory surgeries, the HCPs in ambulatory surgery center have gradually become overworked17 even though we established a special ambulatory surgery follow-up center in our hospital to address patients’ needs after surgery (two nurses are in charge of follow-up-related affairs), which could still not meet all demands. In this case, communication with HCPs through m-health apps may be a compromise to solve this problem to some extent, as this function can fulfill patients’ requirements of communicating with HCPs anytime and anywhere.…”
Section: Discussionmentioning
confidence: 99%
“…The three major ambulatory surgery types performed in the center are laparoscopic cholecystectomy (LC), mammotome minimally invasive (MMT) biopsy and resection of intestinal polyps (RIP). Since an increasing number of surgeries have been performed as ambulatory surgeries, the HCPs in our ambulatory surgery center have gradually become overworked17 Due to this situation, we would like to design an m-health app for ambulatory surgery centers to provide patients with more convenient health-care services and improve the working efficiency of HCPs. Before the m-health app can be systematically implemented, a comprehensive understanding of potential users and user habits is necessary18 M-health apps based on user-centered design have already been proven to be more practical and fully utilized than other m-health apps not designed with a user-centered approach;19,20 thus, surveys of patients’ preferences regarding m-health apps can help effectively design m-health apps and enhance patients’ engagement in m-health app interventions.…”
Section: Introductionmentioning
confidence: 99%